Supply Chain & Logistics of the Ottoman Army (1300-1566) - Haksever, Cengiz (International Journal of Supply Chain Management, 2020)
The Ottoman Empire developed from a frontier principality to become the most powerful empire in the world by 1566. It conquered lands and countries in three continents, covering and area of approximately 978,000 square miles at time of SÃ¼leyman the Magnificent. The most significant conquest, without a doubt, was the capture of Constantinople in 1453 by Mehmet the Conqueror, which marked the end of the Eastern Roman Empire. Historians characterize this event as the end of middle ages. Many historians agree that the Ottomansâ€™ success depended to a large extent on their ability to amply supply provisions and weapons to their soldiers. They also provided plentiful food for their animals which were the main transport means. In other words, although soldiers, Janissaries and cavalry, won battles, the supply chain and logistics of the Ottoman Army made it possible. To the best of the knowledge of the author of this manuscript, there is very little research on how militaries of the middle Ages supplied and logistically supported their soldiers and animals. This paper provides an example of how one of those militaries accomplished it. This research is based on published books and articles by prominent historians and covers the period of 1300 to 1566. It concludes that the basic principles used by the Ottoman Army for their supply chain and logistical activities are still valid today and used by excellent modern supply and logistics systems.